Impact of experimentation in thermodynamic studies of some metallic and oxidic systems - Aune R.E.; Fredriksson P.; Seetharaman S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The importance of experimentation as an ingredient to CALPHAD assessments is brought out in the present paper and is illustrated in the case of a number of metallic and oxidic systems. Two types of experimental techniques have been used in the present laboratory for thermodynamic studies, and the details are presented. The results obtained together with the assessed phase diagram in the case of a few selected systems are presented. It was shown that careful experimentation has brought new features in the case of carbide systems involving Mn, and a new 4-phase equilibrium in the case of Ni-W-O system. New data with regard to the thermodynamic activities of FeO-containing slag systems and sulphide capacities of multicomponent slags, obtained by gas equilibration method, are also presented. A thermodynamic software, THERMOSLAG© based on the experimental data has been found to be extremely useful by the steel industries is also discussed.